ANALYSIS OF RURAL WOMEN’S UNEMPLOYMENT STRUCTURE IN AGRICULTURAL REGIONS BASED ON PRZASNYSZ POVIAT - Winnicka, Beata; Winnicki, Artur (Acta Scientiarum Polonorum. Oeconomia, 2005)
The position of women on Polish labour market is depends on many factors: accepted living style, tradition, habits, external factors which impact on change of approach and behaviour as well as problems concerning raising and educating of new generation. Market transformation causes worse conditions for women than man in professional activity. This article illustrates women’s unemployment rate in Przasnysz Poviat. Moreover, it shows opportunities of this situation’s improvement, especially in rural areas.